Clinicopathologic Features of Two Rare Cases of Dedifferentiated Adamantinomas, Including Diagnostic Implications. (April 2019) - Rekhi, Bharat; Sahay, Ayushi; Puri, Ajay
A dedifferentiated adamantinoma is a rare subtype of an adamantinoma, associated with a relatively aggressive clinical course, with less than 10 such cases reported so far. A 25-year-old-male presented with pain in his right leg of 1-year duration. Imaging disclosed a well-defined lytic, destructive lesion in his proximal tibia with a cortical break and a soft tissue component. Microscopic examination of the biopsy and resected specimen showed nests and clusters of atypical epithelial cells, along with significant areas showing markedly pleomorphic and spindly sarcomatous cells with interspersed mitotic figures and areas of stromal hyalinization. By immunohistochemistry, the areas of epithelial differentiation showed intense positivity for cytokeratin and p63, whereas the sarcomatous areas showed reduced to absent immunostaining. A 51-year-old lady presented with a recurrent tumor in her right tibia, which was initially diagnosed as an adamantinoma, along with metastatic lesions in her lung. Microscopic examination of the recurrent and metastatic tumors showed areas of epithelial differentiation along with spindly sarcomatous cells, arranged in fascicles. By immunohistochemistry, the areas of epithelial differentiation showed positivity for pan cytokeratin. Additionally, p63 was diffusely positive. p53 showed diffuse and intense staining pattern in the sarcomatous component (dedifferentiation). While the first case is disease-free, the second case is on follow-up. The 2 cases of dedifferentiated adamantinoma further confirm the rare occurrence of this tumor in our population. Its correct diagnosis has treatment implications. Differential diagnoses and literature review of similar reported cases are also presented in this article.